Uso de la flora de los traspatios de los barrios suburbanos del norestede la hoya de Loja - Murillo Peñaranda, Cindy Cristina (2015)
study of the flora of the backyards of suburban neighborhoods of northeast basin of Loja, in order to gather information on diversity, uses and cultural importance of the species was performed. It was estimated index of cultural significance (IC) and the informant consensus factor (FIC). The numbers of plants mentioned are also analyzed according to age and education of the informants. 80 interviews were conducted with elderly to 14 years. Of each species was recorded: common name, use and habit. Information 173 species corresponding to 57 families in 5 uses was collected. In general it can be mentioned that there are high FIC values for all categories of use (greater than 0.60 each) indicating an agreement among informants regarding knowledge of plants used in the different categories. The study found that in the study area maintain a wide variety of plants. However, cultural and biological factors threaten the survival of plants in the area